1998
DOI: 10.1161/01.atv.18.5.768
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Viscosity and the Risk of Coronary Heart Disease

Abstract: Abstract-Plasma viscosity is determined by various macromolecules, eg, fibrinogen, immunoglobulins, and lipoproteins.It may therefore reflect several aspects involved in cardiovascular diseases, including the effects of classic risk factors, hemostatic disturbances, and inflammation. We examined the association of plasma viscosity with the incidence of a first major coronary heart disease event (CHD; fatal and nonfatal myocardial infarction and cardiac death; nϭ50) in 933 men aged 45 to 64 years of the MONICA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
38
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(39 citation statements)
references
References 22 publications
1
38
0
Order By: Relevance
“…This important hemodynamic biomarker determines the amount of friction against the blood vessels, the degree to which the heart must work, and the quantity of oxygen delivery to the tissues and organs. It has been reported that elevated blood viscosity is a strong independent predictor for cardiovascular events (Koenig et al, 1998). In the Edinburgh Artery study, it was reported that elevated blood viscosity was the strongest predictor of stroke risk after controlling all other major risk factor (Ciuffetti et al, 2005: Lee et al, 1998.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This important hemodynamic biomarker determines the amount of friction against the blood vessels, the degree to which the heart must work, and the quantity of oxygen delivery to the tissues and organs. It has been reported that elevated blood viscosity is a strong independent predictor for cardiovascular events (Koenig et al, 1998). In the Edinburgh Artery study, it was reported that elevated blood viscosity was the strongest predictor of stroke risk after controlling all other major risk factor (Ciuffetti et al, 2005: Lee et al, 1998.…”
Section: Discussionmentioning
confidence: 99%
“…This effect is most pronounced in tissues where healthy capillaries are essential for unimpaired function such as the kidney, eyes, fingers and toes (Kensey and Cho, 2007;Sloop, 1996). Elevated blood viscosity is a strong independent predictor of cardiovascular events (Koenig et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Increased blood and plasma viscosity has been described in patients with coronary and peripheral arterial disease. The strong positive correlation between plasma viscosity and fibrinogen has been reported in several studies (1,2). Erythrocyte sedimentation rate (ESR) and fibrinogen levels are well known as acute phase reactants.…”
mentioning
confidence: 79%
“…A 1 standard deviation (SD) increase in plasma viscosity (0.070 mPa · s) was associated with a 42 % increase in the relative risk (RR 1.42, 95 %CI, 1.09 -1.86). Comparison of the RR for a CHD event in the top quintile to the risk in the bottom quintile yielded a more than 3-fold increased risk (RR 3.31, 95 % CI 1.19 -9.25) [6].…”
Section: Plasma Viscositymentioning
confidence: 97%